Endometrial aspiration biopsy (EAB) as diagnostic tool of ultrasound suspicious endometrial lesions in women without abnormal bleeding - Surkont, Grzegorz; Wlaźlak, Edyta; Bitner, Adam; Stetkiewicz, Tomasz; Topczewska-Tylińska, Katarzyna; Suzin, Jacek (Menopause Review/Przegląd Menopauzalny, 2006)
Nowadays transvaginal sonography (TVS) is often used in everyday clinical practice for endometrial carcinoma screening, despite the fact that there is no proof that TVS is useful for that purpose. Because TVS is used for endometrial carcinoma screening ”out of label”, it would be advisable to use minimally invasive methods to verify suspicious ultrasound results. Aim of the study: To evaluate the usefulness of endometrial aspiration biopsy (EAB, Pipelle) to obtain enough tissue for a histopathologic verification of suspicious ultrasound pictures of the endometrial cavity in women without abnormal bleeding. Material and methods: We analysed 57 postmenopausal women who were referred to the Clinic of Operative Gynaecology and Gynaecologic Oncology for an invasive evaluation because of suspicious ultrasound endometrial pictures and in whom we decided to perform EAB (I group). A comparative group consisted of 124 women, in whom we used EAB to verify abnormal bleeding. Results: In the first group, in 50.9% of cases, we obtained enough tissue to produce a diagnosis. In the second group, 78% biopsies gave enough tissue to obtain a diagnosis. In the first group, in 5.56% of cases, there was no possibility to enter the endometrial cavity. In the second group, in 0.81% of women, we had problems with entering the uterine cavity with the Pipelle. Discussion: EAB is a minimally invasive method to obtain endometrial samples for a histopathologic evaluation. Endorette seems to be a useful tool to verify suspicious endometrial ultrasound pictures. However, among women without abnormal bleeding in about 50% of cases we may expect not enough tissue to give a histopathologic diagnosis. Nevertheless, a lack of tissue does not mean that there is no disease present in the uterine cavity. Therefore, there is usually a need to continue diagnostics using more invasive methods. The whole diagnostics process may not give enough tissue to make a diagnosis, which may lead to do hysterectomy in healthy woman. We should remember about this when in the case of ”out of label” use of TVS for endometrial carcinoma screening, we write that there is a suspicion of endometrial disease.